Mediasi Antarbudaya Untuk Pencegahan Stres Akulturasi Pada Mahasiswa Urban - Andhika Yudha Pratama; Saputra, Meidi; Mawarti, Rista Ayu; Sudirman, Sudirman (Jurnal Civic Hukum, 2023)
Intercultural mediation is considered to be one of the approach disciplines in building good and positive relations between multicultural community spaces. This approach places great importance on a dialogical space that involves social groups with equal principles. Therefore, this approach is very much needed in the composition of a society that has diverse cultures. One of how the diversity of the community is built is the relationship between urban groups of students and residents. In several cities in Indonesia, the composition of the two in terms of numbers shows a very large number. This study seeks to explain the importance of intercultural mediation as a priority need to create a harmonious space in society. This needs to be studied because in many cases it is difficult for urban students to blend in with their new environment so they experience acculturation stress which leads to conflict and failure to study. This research will be conducted using a qualitative method with a case study approach. Exploration of cases regarding the symptoms and facts of acculturation stress that have been experienced by students is the main narrative in this study. Case studies that occur in the largest urban students destinations such as Yogyakarta, Surabaya, Jakarta, Malang, and Bandung will be the main focus of the search. This study will present a narrative about the strong relationship between intercultural mediation as a solution to the problem of cultural acculturation stress in urban student groups. The existence of a dialogue room that focuses on cultural recognition and social understanding between groups available in cities where many students come needs to be created and improved. Many ways can be done such as student day programs on campus with a duration of up to two semesters, community involvement around campus in new student orientation programs, and cultural festivals, policy making from the local government that regulates urban student administration. It is hoped that this study will become an important study for the community, universities, and all stakeholders to design preventive efforts through the development of various models of intercultural mediation implementation so that acculturation stress in urban students can be minimized.